Uninephrectomy-Induced Lipolysis and Low-Grade Inflammation Are Mimicked by Unilateral Renal Denervation - Arsenijevic, Denis; Cajot, Jean-François; Fellay, Benoit; Dulloo, Abdul G.; Van Vliet, Bruce N.; Montani, Jean-Pierre (Frontiers in Physiology, 2016)
Uninephrectomy (UniNX) in rats on a fixed food intake leads to increased lipolysis and a low-grade inflammation with an increased subset of circulating cytokines. Because UniNX ablates renal nerves on the side of the removed kidney, we tested the contribution of unilateral renal denervation in the phenotype of UniNX. We compared Sham-operated controls, left nephrectomy (UniNX) and unilateral left kidney denervation (uDNX) in rats 4 weeks after surgery. uDNX did not affect kidney weight and function. In general, the uDNX phenotype was similar to the UniNX phenotype especially for lipolysis in fat pads and increased low-grade inflammation. uDNX led to decreased fat pad weight and increased hormone sensitive lipase and adipocyte triglyceride lipase mRNA levels in epididymal and inguinal adipose tissue, as well as increased circulating lipolysis markers -hydroxybutyrate and glycerol. Measured circulating hormones such as leptin, T3 and insulin were similar amongst the three groups. The lipolytic cytokines interferon-gamma and granulocyte macrophage colony stimulating factor were increased in the circulation of both uDNX and UniNX groups. These two cytokines were also elevated in the spleen of both groups, but contrastingly they were decreased in fat pads, liver and kidneys. Both uDNX and UniNX similarly increased noradrenaline content in fat pads and spleen. Melanocortin 4 receptor mRNA levels were increased in the brains of both uDNX and UniNX compared to Sham and may contribute to increased tissue noradrenaline levels. In addition, the farnesoid X receptor (FXR) may contribute to changes in tissue metabolism and inflammation, as anti-inflammatory FXR was decreased in the spleen but increased in other tissues in uDNX and UniNX compared to Sham. In summary, both uDNX and UniNX in rats promote metabolic and immunological alterations by mechanisms that seem to implicate modification of unilateral renal nerve pathways as well as central and peripheral neural pathways.